Patient characteristics and satisfaction across different dimensions of healthcare for tuberculosis: A study at Puskesmas Polonia, Medan - Riani, Riani; Siagian, Masryna; Siregar, Santy Deasy (Buletin Kedokteran & Kesehatan Prima, 2025)
Background: High-quality healthcare is vital for effective TB management. Patient satisfaction reflects service quality and influences treatment adherence. This study investigates the characteristics and satisfaction levels of pulmonary TB outpatients at Puskesmas Polonia, Medan, a high-burden facility. Aims: To describe the demographic characteristics of TB patients and analyze their satisfaction across various healthcare service dimensions (tangibles, reliability, responsiveness, assurance, empathy, and operational satisfaction). Methods: A cross-sectional study was conducted from December 2024 to January 2025, involving 82 pulmonary TB outpatients selected via purposive sampling. Data on patient characteristics and satisfaction (overall and by dimension, using a dichotomous scale) were collected through questionnaires and analyzed using univariate statistics. Results: The majority of the 82 TB patients were male (63.4%), with the largest age groups being 21-30 and 31-40 years (24.4% each). Most had upper secondary education (32.9%). Overall, 76.83% of patients reported satisfaction. Satisfaction levels varied across dimensions: assurance (83.0%) and reliability (79.0%) were highest, while operational satisfaction (67.0%) and responsiveness (71.0%) were lower. Conclusion: While overall satisfaction was high, specific service dimensions, particularly operational processes and responsiveness, require attention to enhance the patient experience for TB patients at Puskesmas Polonia. These findings can inform targeted interventions to improve service quality and support TB control efforts.